The Determinants of International Tourism: Evidence from European Countries and China’s Provinces - Cheng, Zhang; Nahar, Faiza Husnayeni (Jurnal Ekonomi & Studi Pembangunan, 2022)
Tourism has been reported as one of the largest economic sectors in the world. It is shown by more than hundreds of jobs involved in this sector which directly escalate the welfare and economic growth of a country. Thus, government will support any actions that could improve competitiveness and profitability of tourism industry. The main objective of this paper is to determine the significant factors of international tourism receipts by 18 European countries and 12 provinces of Western China between 1995 and 2019. Based on data, Europe known as the world’s largest international tourist receipt in 2019 followed by Asia and the Pacific including China. It is interesting to note that China, particularly in western part, has contributed more on achieving tourism receipt. China has potential to grow its tourism sector in significant trend due to its large land size and massive human resources that might further defeat Europe’s total tourist receipt. By using panel Autoregressive Distributed lag (ARDL) model, there would be different responses related to determinant factors of tourism over long run and short run. The result revealed that population, carbon dioxide emission and trade openness have positive effect to the international tourism receipt in Europe in the long run while the rest explanatory variables such as transportation infrastructure and energy consumption have negative effect to the international tourism receipt in Europe. While in case of China, population and energy consumption are statistically significant and positive to international tourism receipt in the long-run correlation, but the rest variables are having negative effect. Unfortunately, in the short-run effect, it was found that all variables are not statistically significant at least at the ten percent significance level in both Europe and China. From the result, the Europe and Chinese policy makers can evaluate the policy based on each result. For instance, the fact that the high level of population density could reach larger tourism receipt is not always true, government need to provide some training for the party who will be involved in tourism industry to gain knowledge and encourage them to be more creative and innovative. Hence the good quality of listed tourism destination would attract more tourist to the destination country